Investigating the role of case markers in honorific agreement processing in Korean - Lee, So Young; Yoo, Myung Hye (Proceedings of the Linguistic Society of America, 2024)
This study explores the influence of case markers on the attraction effect in subject-verb honorific agreement in Korean. Using a self-paced reading experiment on PCIbex Farm, we manipulated case markers (possessive vs. nominative) and the presence of the honorific marker -si on verbs to assess their impact on the attraction effect, where syntactically illicit NPs are erroneously retrieved due to partial feature matching. While Avetisyan et al. (2020) reported that in Armenian, case information is used as a retrieval cue during subject-verb number agreement, our preliminary findings reveal no significant attraction effect related to case marker similarity, indicating that the case features (nominative case) do not crucially trigger the attraction effect in honorific agreement. The discrepancy with previous studies highlights the role of noun animacy and the specific construction of Korean sentence structure. Our results contribute to understanding the nuanced factors influencing honorific agreement processing in Korean and suggest that case marking, while integral to sentence structure, does not significantly affect the attraction effect in honorific agreement processing.